Haemodynamic Response After induction of Anaesthesia in Patients undergoing Coronary Artery Bypass Grafting Surgery of Poor Left ventricular Function. A comparison between Thiopental / fentanyl and Etomidate / fentanyl (BIRDEM Medical Journal, 2013)
Objective: To compare the haemodynamic effect of thiopental/fentanyl with etomidate/fentanyl during anaesthetic induction in patients with coronary artery disease with poor left ventricular function (ejection fraction < 45%). Design: A retrospective randomized trial. Setting: Ibrahim Cardiac Hospital and Research Institute. Participants: Twenty patients with coronary artery disease of poor left ventricular function (ejection fraction